2019
DOI: 10.1002/mgg3.803
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of people with inherited retinal conditions toward gene editing technology

Abstract: Background The views of people with genetic conditions are crucial to include in public dialogue around developing gene editing technologies. This qualitative study sought to characterize the attitudes of people with inherited retinal conditions (retinitis pigmentosa [RP] and Leber congenital amaurosis [LCA]) toward gene editing. Methods Individuals with RP ( N = 9) and LCA ( N = 8) participated in semi‐structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Previous research on screening attitudes among families and individuals living with different types of genetic condition has revealed some common themes in their responses to screening. Research exploring the views of people and families living with conditions as diverse as spinal muscular atrophy (Boardman et al., 2017) and inherited retinol conditions (Hoffman‐Andrews et al., 2019), for example, demonstrates that despite the wide spectrum of impairment effects associated with these conditions, common themes can be identified. These themes include a querying of presumed low quality of life with genetic disease (Boardman & Hale, 2018; Hoffman‐Andrews et al., 2019), the role of social factors—notably stigma and environmental barriers—in shaping life experiences (Boardman et al., 2020), the dire need for greater public awareness of the condition (Boardman & Hale, 2018), and the key role of expressivist concerns in framing screening responses (Hoffman‐Andrews et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on screening attitudes among families and individuals living with different types of genetic condition has revealed some common themes in their responses to screening. Research exploring the views of people and families living with conditions as diverse as spinal muscular atrophy (Boardman et al., 2017) and inherited retinol conditions (Hoffman‐Andrews et al., 2019), for example, demonstrates that despite the wide spectrum of impairment effects associated with these conditions, common themes can be identified. These themes include a querying of presumed low quality of life with genetic disease (Boardman & Hale, 2018; Hoffman‐Andrews et al., 2019), the role of social factors—notably stigma and environmental barriers—in shaping life experiences (Boardman et al., 2020), the dire need for greater public awareness of the condition (Boardman & Hale, 2018), and the key role of expressivist concerns in framing screening responses (Hoffman‐Andrews et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that the ‘expressivist objection’ to prenatal testing and screening may be perceived and experienced in different ways across disabilities. While it has long been acknowledged that the nature of an impairment (in particular its age of onset and its relative stability over time) has a significant impact on the degree to which disabled people incorporate it into their identity and sense of self (Bogart et al., 2017; Hoffman‐Andrews et al., 2019), this study suggests that other impairment variables, specifically whether the impairment is physical or cognitive in nature, may also impact the degree to which expressivist concerns around genetic screening are experienced, interpreted, and responded to. While previous research has demonstrated that the higher the degree of perceived integration between self and impairment, the greater the significance of expressivist concerns within reproductive views and decisions (Boardman & Hale, 2018), this study adds that for conditions that affect behavior and personality, the blending of personhood with condition results in very particular experiences with expressivist concerns and, consequently, strategies of deflection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the reasons involved emotional reactions (the 'yuck' and 'wow' factors), possible long-term consequences for society, the unnaturalness of the technology, and unacceptable health risks. In addition, there are studies on public attitudes regarding CRISPR-Cas9, gene editing, or gene modi cation focusing on speci c applications-e. g., hereditary eye diseases [15] or non-human applications such as GM foods [16,17].…”
Section: Public Discourse On Crispr-cas9mentioning
confidence: 99%
“…Important research questions include a better understanding of citizens' perspectives on CRISPR-Cas9, its uses, and embedding in society in relation to the array of hereditary conditions it could be used for. There is already some research on this [15], but more research is needed for a better understanding. In particular research could delve deeper in the way citizens make sense of the technology, how they process new information about the latest developments -breakthroughs or crises-and how they can contribute to the technology in co-creation processes.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%